Cloning and characterization of newly isolated lipase from Enterobacter sp. Bn12 - Farrokh, Parisa (Sociedade Brasileira de Microbiologia, 2014)
A mesophilic Enterobacter sp. Bn12 producing an alkaline thermostable lipase was isolated from soil in Tehran, Iran. The lipase gene (ELBn12) was identified from a genomic library. Sequence analysis of the DNA fragment revealed an open reading frame of 879 bp encoding a lipase with a molecular mass of 31.3 kDa. The deduced amino acid sequence showed 96% identity with a lipase of Enterobacter sp. Ag1 and the identity of their DNA sequences was 88.9%. ELBn12 belongs to the lipase subfamily I.1 and its catalytic triad consists of Ser82, Asp237 and His259. The lipase was expressed in Escherichia coli (BL21) pLysS and partially purified by anion exchange chromatography. The maximum activity of ELBn12 was obtained at temperature of 60 °C and pH 8.0 towards tricaprylin (C(8)) and its specific activity was around 2900 U/mg. ELBn12 was stable within a broad pH range from 6.0 to 11.0. The enzyme showed high stability in both polar and nonpolar organic solvents at 50% (v/v). The lipase activity was enhanced in the presence of 10 mM of Ca(2+), Mg(2+) and K(+), while heavy metals (Fe(3+) and Zn(2+)) had strong inhibitory effect. ELBn12 showed high activity in the presence of 1% (w/v) nonionic surfactants, however ionic surfactants inhibited the lipolytic activity. ELBn12 characteristics show that it has a potential to be used in various industrial processes.